2016
DOI: 10.1002/zaac.201600161
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Various Substituents on the Density of Tetrazolium Nitrate Salts as Green Energetic Materials

Abstract: The substitution effect of various functional groups such as -NO 2 , -CN, -N 3 , -NF 2 , and -NH 2 on the density of tetrazolium nitrate salts is investigated through multiple linear regression method. The methodology of this work introduces a new model, which related density of tetrazolium nitrate salts to the number of fluorine and nitrogen atoms, the presence of NF 2 groups, NO 2 groups, as well as CH 3 groups in the structural formula. The new reliable correlation shows that the NF 2 and NO 2 group can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The effect of some functional groups like –NO 2 , –CN, –N 3 , –NF 2 and –NH 2 on the density of tetrazolium nitrate salts is investigated through multiple linear regression method …”
Section: Introductionmentioning
confidence: 99%
“…The effect of some functional groups like –NO 2 , –CN, –N 3 , –NF 2 and –NH 2 on the density of tetrazolium nitrate salts is investigated through multiple linear regression method …”
Section: Introductionmentioning
confidence: 99%
“…From the increasing relative ratio n O to n N it can be concluded that there is probably NO 2 substitution in the molecule. Based on previous reports it is known that the introduction of some substituents such as NF 2 , NO 2 , and N 3 in the molecular structure of nitrogen rich compounds can enhance their density due to probable formation of strong π bonds between tetrazole ring and substituent , . In this work, we found that the presence of nitroimino functional groups in the azole‐based energetic compounds increase their density.…”
Section: Resultsmentioning
confidence: 50%
“…The presence of a large number of energetic N–N and N–C bonds in the structure of these compounds causes to high positive formation heat and a large amount of hydrogen bonds, which in turn can result in their low sensitivities, good thermal stabilities, and relatively high densities , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several publications which have used QSPR approaches to predict the relationship between different physicochemical properties of energetic materials. Such as studying of various physicochemical properties of ionic liquids through QSPR approaches [21][22][23][24] or studying the effect of different specific structural parameters on density of various type of energetic materials [25][26][27].…”
Section: Introductionmentioning
confidence: 99%